Acute pain management in rheumatoid arthritis - Abdullah, Hilmi (2014)
This lecture described the following: 1. Diagnosis and pathophysiology of RA 2. Drugs used in pain management e.g. steroids, NSAIDs etc 3. Non pharmacological aspects of management